Morphological optimization of female combat sports athletes as seen by the anthropologists - Burdukiewicz, Anna; Pietraszewska, Jadwiga; Andrzejewska, Justyna; Stachoń, Aleksandra (Anthropological Review, 2016)
Body build and proportions are key determinants of athletic success. The effects of the athlete selection process and discipline-specific training are differentiated body dimensions. The aim of the study was to examine the physical characteristics of female combat athletes. The results of anthropometric measurements of 154 females aged 21.2±1.79 years competing in judo, jiu-jitsu, karate, taekwondo, and fencing for 7.5±3.43 years. Significant differences were observed between the judo and karate, taekwondo and fencing practitioners in chest, hip, arm and forearm girths. More variance was observed in body proportions. Fencers had the slimmest body shape, a more massive body size in the judokas. Longer upper extremities relative to lower extremity length were found in the jiu-jitsu group. Relative to body height, a larger torso and greater girths were observed in the judokas compared with the fencing, karate, and taekwondo practitioners. The groups did not differ in the level of endomorphy. Mesomorphy was highest in judokas and the lowest in fencers, although ectomorphy was most dominant in the latter group. Females practitioners of combat sports exhibit differences in physical characteristics as an effect of optimizing body type and build via the training and athlete selection process of a given discipline. The anthropometric measures could play a role in talent identification programmes for martial arts and help the trainers to optimize the motoric effectiveness of athletes.